The Impact of Tourism Development on The Globalization of Markets and Economic Activity (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2023)
Tourism as a sphere of economic activity is being widely developed in the modern world. According to experts of the World Bank Institute, tourism today ranks second in the world economy after mechanical engineering in terms of sales and occupies a leading place among other service industries. The tourism market today is not only one of the most globalized markets but the development of tourism contributes even more to the globalization of markets and economic activities. A wide variety of products can be created within the framework of the global tourism industry which are based for the most part on various features of the territory in which they are sold, as well as various combinations of goods and services provided to customers. Therefore, a very wide range of tourism products can be created even within a specific territory, each of which will be focused on its target audience of consumers. Some types of tourism require expensive and highly organized tourist infrastructure and high-quality services, while others can develop in conditions of almost complete absence of them. In both cases, tourism is considered a sphere of economic activity that can give an incentive to the development of a territory's economy and create the necessary conditions for its growth.
Keywords: Tourism; Quality of services; Tourist infrastructure; Region; Economic activity